Modified Buccal Fat Pad Reduction as a Component of Perioral Mound Rejuvenation “The Mouth Pouch” - Caughlin, Benjamin P.; Abud, Brittany (Facial Plastic Surgery, 2025)
To evaluate the effectiveness of a comprehensive surgical approach addressing perioral mounds—the “mouth pouch”—through modified buccal fat pad sculpting, targeted mucosal and muscle resection, and focal skin tightening for enhanced lower facial contouring.Conventional techniques often fall short in resolving contour irregularities in the perioral region due to intricate anatomy and high functional mobility.The perioral area includes a complex interplay of superficial and deep fat compartments, musculature, vasculature, and nerves. Aging-related atrophy of superficial fat and pseudoherniation of buccal fat contribute to soft tissue compartmentalization and visible mounding.Radiofrequency-assisted dermal tightening is combined with intraoral fat sculpting to promote further definition.Ideal candidates have distinct perioral mounds, robust buccal fat pads, thickened oral mucosa, and visible lines of parakeratosis.A seven-step intraoral technique under local anesthesia include mucosal resection, buccinator stripping, buccal fat pad sculpting, and radiofrequency treatment.Dual compression with intraoral packing and external head wrap minimizes hematoma and infection risk.Combining bony augmentation (e.g., chin implants) with soft tissue contouring yields comprehensive lower face rejuvenation.This technique for treating perioral mounds, in carefully selected patients, provides a reproducible, and safe method for lower facial contour enhancement.
Keywords: perioral mounds; buccal fat pad sculpting; lower facial rejuvenation; facial contouring; oral mucosa resection